Mapping well-being in France - Murtin, Fabrice (OECD Papers on Well-being and Inequalities, 2024)
This paper provides two innovative measures of well-being for French communes, namely a well-being aggregate index and an index of multi-dimensional poverty. These measures provide an unprecedented view of well-being at the local level by using 7 of the 11 key dimensions of the OECD Better Life Initiative (income, unemployment, housing, education, civic engagement, health and environmental quality). The results show that joint deprivation in at least five dimensions of well-being is starkly concentrated among 316 communes, representing as many as 5.2 million inhabitants (7.7% of the French population)